Persepsi Pendengar Terhadap Rebranding Radio Metta FM Solo - Ancika, Nurmalita Anggie; Suryo, Herning; Kusumo Aji, Haryo (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
Radio Metta Solo FM was founded in 2003 as a Catholic radio which facilitates many Catholic activities and broadcasts around 30% of spiritual programs that focus on the spiritual needs of the community. Over time, this radio began to transform into a professional commercial radio that focused on advertising and profit-oriented activities. This radio is rebranding to Urban Family Radio, with a change in name and tagline that reflects its new identity as a modern and urban family radio. The aim of this research is to determine the perception of the rebranding carried out by Radio Metta Solo FM by listeners in Surakarta. The supporting theories in this research are Rebranding according to Muzellec and Lambkin and Perception according to Walgito. This research is descriptive with qualitative methods. The results of this research conclude that the rebranding of Radio Meta FM Solo produced varying impacts on listener perceptions. The change to more modern content has succeeded in attracting new listeners with a fresh and contemporary approach. However, there are challenges in maintaining radio's original identity, leading to a decline in the loyalty of long-time listeners. It is important for Radio Meta FM Solo to clarify market segmentation and maintain elements that are loved by long-standing listeners so that brand perception remains positive and consistent, allowing this radio to develop without losing the essence that its loyal listeners have known. Keywords: Rebranding, Perception, Radio Metta FM Solo